2012
DOI: 10.1158/2159-8290.cd-12-0107
|View full text |Cite
|
Sign up to set email alerts
|

CD36 Repression Activates a Multicellular Stromal Program Shared by High Mammographic Density and Tumor Tissues

Abstract: Although high mammographic density (MD) is considered one of the strongest risk factors for invasive breast cancer, the genes involved in modulating this clinical feature are unknown. Tissues of high MD share key histological features with stromal components within malignant lesions of tumor tissues, specifically low adipocyte and high ECM content. We show that CD36, a transmembrane receptor that coordinately modulates multiple pro-tumorigenic phenotypes including adipocyte differentiation, angiogenesis, cell-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
159
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(175 citation statements)
references
References 50 publications
13
159
1
2
Order By: Relevance
“…This observation, paired with a similar characterization observed in stromal tissue adjacent to tumors, led DeFilippis et al [50] to examine and compare molecular characteristics of fibroblasts from breast tissue of high and low mammographic density. Gene expression profiling of fibroblasts from high and low density revealed the greatest difference in expression for CD36; CD36 was down-regulated approximately 4-fold in high-density-associated fibroblasts relative to those from the low-density fibroblasts.…”
Section: Experimental Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…This observation, paired with a similar characterization observed in stromal tissue adjacent to tumors, led DeFilippis et al [50] to examine and compare molecular characteristics of fibroblasts from breast tissue of high and low mammographic density. Gene expression profiling of fibroblasts from high and low density revealed the greatest difference in expression for CD36; CD36 was down-regulated approximately 4-fold in high-density-associated fibroblasts relative to those from the low-density fibroblasts.…”
Section: Experimental Studiesmentioning
confidence: 84%
“…Data from both epidemiological and experimental studies suggest several plausible mechanisms, including increased local estrogen production, altered levels of growth factors (e.g., increased IGF-1 expression and decreased TGFβ expression), decreased CD36 expression and changes in mechanical properties 7. Although mammographic density is associated with the degree of lobular involution, they appear to be independent risk factors for breast cancer GWAS genome-wide association studies, SNPs single nucleotide polymorphisms increased matrix accumulation [50]. Interestingly, there are in vitro data to suggest that CD36 expression can be increased by common drugs such as aspirin [53] and statins [54].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Gene set enrichment analysis (GSEA) reveals the biological processes activated in HD fibroblasts: The stress response, inflammation, stemness, and growth factor signaling To determine the biological processes that are activated in HD fibroblasts, we re-interrogated genome-wide transcriptional profiling data 8 obtained from LD mammary fibroblasts (n = 6 patients) and HD mammary fibroblasts (n = 7 patients) from a series of 13 female patients (Table S1). These fibroblasts were derived from disease-free breast biopsies.…”
Section: Resultsmentioning
confidence: 99%
“…A potential marker of risk (CD36) was recently reported by the Tlsty laboratory. 8 Yang et al, 2010 and colleagues 9 reported a reduction in expression of the TGF-β gene and an increase in Cox-2 in high-density tissue (with histologically normal epithelia) taken 5 cm or more away from an infiltrating carcinoma, compared with low-density cancer-associated stroma. However, it remains largely unknown what biological processes are involved in high mammographic density and its effects on breast cancer risk.…”
Section: E-06mentioning
confidence: 99%
“…Could transient inhibition of a key signal translate into risk reduction for children after exposure? New studies show that stromal cells from mammographically dense breast executing a CD36 dependent program that is permissive for cancer provide a novel target for reducing cancer risk via the microenvironment (85). Even established disease can be suppressed or normalized by rewiring the signals from the microenvironment (86), thus it is likely that normalizing the microenvironment after an exposure or event could restore control of aberrant cells.…”
Section: Implications For Cancer Preventionmentioning
confidence: 99%